Theoretical Analysis of Invariant, Subinvariant and Variative Components of Inorganic Substance Properties - Kholmurodova Laziza Erkinovna (Genius Publishing Group, 2023)
Theoretical analysis of invariant, subinvariant and variative components of the properties of inorganic matter, the article considers these principles.
Keywords: inorganic substance; inorganic substance properties; subinvariant component; variative component